Perception of inherited risk in type 2 diabetes: a systematic review - Elisa Airikkala; Elisa Airikkala; Mari Laaksonen; Mari Laaksonen; Arja Halkoaho; Marja Kaunonen; Marja Kaunonen (Frontiers in Public Health, 2023)
IntroductionA family history is impacting the individual’s risk perception. The objective of this systematic review was to describe inherited risk perceptions of type 2 diabetes from the citizen’s viewpoint. The aim was to summarize and increase understanding so that the increased knowledge could be used effectively in type 2 diabetes risk communication in health care.MethodsWe conducted a systematic review using CINAHL, Medline, and Scopus databases for hereditary, risk, perception, and diabetes related concepts, within the date range of 1.1.2017 to 2.8.2022. Eligible articles were English, peer-reviewed, and addressed the research question: how is hereditary risk of type 2 diabetes perceived? Returns were viewed independently by two authors, and evaluated using the appraisal criteria of the Joanna Briggs Institute. A thematic analysis was used for the synthesis of the data, yielding three themes describing perceptions of inherited risk in type 2 diabetes.ResultsA total of 32 articles were included, of which 23 were quantitative, 5 qualitative, and 4 were mixed-methods studies. The extracted themes were (1) Identifying heredity as a risk factor, (2) Diversity of hereditary risk, and (3) Perception of the magnitude of personal risk.DiscussionThe perception towards hereditary risk can vary from a desire to actively make a lifestyle change, to the view that diabetes is inevitable regardless of lifestyle. A positive family history increases the risk perception of type 2 diabetes, but the perceived magnitude of the risk may vary from person to person. The findings have the potential to be applied in healthcare’s risk communication.